Epistemic Distortion in Qur’anic Interpretation: Hustle Culture and Digital Religious Narratives on Instagram - Kamil, M. Ilham; Langaji, Abbas; Ilham, M.; Harun, Amrullah; Anggoro, Muhammad Rake Linggar (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2025)
This study uses qualitative methods, combining textual and visual analyses, to investigate how Qur’anic verses are interpreted, manipulated, and circulated in frenzied cultural narratives on Instagram. This research focuses on the content of three Instagram accounts: @alqurancustomku, @lanternoflightofficial, and @ssheikh00, supported by secondary literature on Islamic epistemology and digital religion. The study finds that Qur’anic interpretations on these platforms often reflect selective reading and cherry-picking of verses that support entrepreneurial and motivational narratives, frequently detaching scriptural meaning from scholarly traditions. Authority over interpretation shifts from ulama to digital influencers, creating a fragmented epistemic environment that privileges virality over exegetical rigor. This research contributes to the growing field of digital religion by articulating how algorithm-driven content production facilitates new forms of textual reception, theological authority, and spiritual branding. It integrates insights from the theory of text reception and epistemic distortion to frame this trend as a reconfiguration of Qur’anic meaning under the pressures of digital capitalism. The findings call for greater literacy in Qur’anic hermeneutics within digital media spaces and encourage religious authorities, educators, and policymakers to develop guidelines for ethical and theologically sound online da’wah practice. This study focuses on a small number of Instagram accounts and does not fully explore platform-based variation (e.g., TikTok, YouTube) or broader demographic responses, such as youth and inter-sectarian interpretations. Future research should expand the comparative scope and include quantitative engagement metrics